(untitled) (International journal of artificial intelligence, 2025)
Liver steatosis (fatty infiltration) and its subsequent stages—steatohepatitis, fibrosis, and cirrhosis—are considered one of the most pressing global health issues today. According to recent epidemiological data, non-alcoholic fatty liver disease (NAFLD), the most common form of these conditions, affects over 1.5 billion people worldwide, with projections estimating a rise to 33% of the global population by 2030 (Younossi et al., 2019). This article analyzes the pathological foundations of liver diseases, morphological changes, diagnostic criteria, and clinical significance. Additionally, modern non-invasive methods of diagnosis, genetic and molecular mechanisms, as well as promising treatment directions are discussed. The article deeply illuminates the pathophysiology, histopathology, and clinical manifestations of liver diseases, while reviewing modern diagnostic and treatment methods, supported by key statistical insights into prevalence, progression rates, and outcomes.